The middle-development trap on human development - Korhonen, Bruna Milagres (2021)
The ongoing discussion about connections and differences between basic needs and basic human rights seems to not be any close to a conclusion. Notwithstanding, human development activities are based on them, and use those definitions to develop and promote human development projects and establish human development programs. Using the idea of the theoretical economic middle-income trap, I argue in this paper that human development activities fall into a middle-development trap when trying to work beyond the basic needs towards human development and I attempt to point out, using a human development program as a study case, that the confusion between the achievement of basic needs and/or basic human rights is the core issue for this middle-development trap.